Can the balance evaluation systems test be used to identify system-specific postural control impairments in older adults with chronic neck pain? - Madsalae, Thanya; Thongprong, Tanapat; Chinkulprasert, Chatchada; Boonsinsukh, Rumpa (Frontiers in Medicine, 2022)
Background Older adults with chronic neck pain (CNP) demonstrate impaired postural control. The Balance Evaluation Systems Test (BESTest) is used to assess systems underlying postural control impairments, but its use in CNP has not been reported. This study assessed whether the BESTest can identify postural control impairments in CNP as well as the level of BESTest item difficulty by Rasch analysis. Materials and methods This cross-sectional study recruited thirty young adults (YOUNG) aged 20–40 years and eighty older adults aged 60 years or older [without neck pain (OLD) = 60, with chronic neck pain (CNP) = 20]. Questionnaires were administered to collect demographic data, intensity of neck pain (VAS), patient’s self-rated neck pain and disability (NDI), and balance confidence in daily activities (ABC). The BESTest was used to assess postural control. Results The CNP group showed the lowest ABC scores. Compared to the YOUNG group, the BESTest score was significantly lower in the OLD group, while the CNP group showed the lowest score, suggesting that balance control deteriorated from the normal aging process and further declined in the CNP group, especially in biomechanical constraints, transitions–anticipatory postural adjustment, and reactive postural response (p < 0.05). Using scores from these three sections, the BESTest was accurate at the cutoff score of 48.5 out of 51 for differentiating the older adults whose daily life are affected by neck problems (using the NDI as a reference) with a high AUC (0.79), sensitivity (72%), and specificity (69%). The Rasch analysis revealed that the Timed Up and Go with dual task test was the most difficult BESTest item for all groups, whereas 14 items showed more difficulty for the CNP group. Conclusion The BESTest can be used to identify postural control impairments in CNP patients, even those with moderate pain and mild disability with a high level of physical functioning. The combined score of biomechanical constraints, transitions–anticipatory postural adjustment, and reactive postural response domains was suggested for the detection of older adults whose daily lives are affected by neck problems. This will also help clinicians consider the management of neck pain to prevent falls in CNP.